Analisis Hukum Keluarga Islam Terhadap Problematika Perkawinan Usia Dini: Studi Kasus Di Kantor Urusan Agama Kecamatan Bengkalis Kabupaten Bengkalis - Nur Faiza; Juwandi Juwandi (Al Fuadiy Jurnal Hukum Keluarga Islam, 2024)
The problem in this study is about how the analysis of Islamic Family Law on the problems and factors that cause early marriage. The purpose of this study is to determine the analysis of Islamic Family Law on the problems and factors that cause early marriage in the District of Bengkalis. This type of research is Field research. The data sources used are primary and secondary data sources. And in the technique of collecting data using the method of observation, interviews, and documentation. DSTA technical analysis used is data reduction, data presentation, and conclusion. The results of the study can be stated that the analysis of Islamic Family Law on the problems of early marriage often involves ethical considerations, child welfare, and physical and mental readiness of couples who want to get married. For example, early marriage that is too young can result in physical and mental health risks for both parties, and can interfere with education, potential poverty and personal development. Factors causing early marriage are matchmaking factors, self-will factors, and promiscuity factors.